Identifying the Characteristics of Educational Influential Nurses: A Qualitative Study - Mostafa Shokohi; Ali Akbar Haghdost; Reza Majdzadeh; Forough Reiani (Strides in Development of Medical Education, 2013)
Background & Objective: Educational influentials (EIs) are individuals who can positively influence their peers These individuals play a key role in knowledge transfer and knowledge translation process Having knowledge of their characteristics is very important in detecting these people There is a paucity of information in the medical field especially in nursing regarding this context The aim of this study was to find the main features of an EI nurse in a local hospital setting Methods: This research was a qualitative study that was performed by a focus group discussion (FGD) method Sixteen nurses who worked in Afzalipour Hospital affiliated with Kerman University of Medical Sciences Iran were selected The main question was “when you face a clinical problem who do you consult with for the answer?” which meant “what kind of characteristics does this person have?” The content of the interview was recorded and analyzed by content analyses method after documentation and finally main themes and their subcategories were obtained Results : The main characteristics of EL nurses were classified as following: high knowledge communicative skills decisionmaking humanistic behaviors and clinical experience and skills Conclusion: Apart from clinical experience and skills the other characteristics identified for EI nurses were obtained in other studies The new feature that is explored in this study may indicate the fact that clinical skills and experiences have an important role among nurses